Малогабаритный стробоскопический блок с пониженным энергопотреблением - Рубан, В.П.; Холод, П.В. (Технология и конструирование в электронной аппаратуре, 2003)
Рассматриваются пути уменьшения напряжения питания, понижения энергопотребления, уменьшения габаритов стробоскопического блока. Предложенные решения позволяют понизить напряжение питания стробоскопического блока до ±5 В, уменьшить потребляемый ток до 62,3 мА. Предлагается в целях уменьшения габаритов блока использовать формирователь строб-импульсов на щелевой линии, что дает возможность разместить стробоскопический блок в объеме 30×120×10 мм. The present work is devoted to the analysis of ways of supply voltage decreasing, power consumption reduction and the strobe unit downsizing. For reducing the supply voltage down to ±5 V the comparator time instability falls to 3,6 ps. To decrease the consumption current the sampling gate is made by the symmetric bridge circuit, and the strobe pulse generator is activated by nanosecond pulses. The consumption current of the strobe unit decreases to 62,3 mA at that. It is proposed to use a slotline strobe pulse shaper for downsizing the strobe unit. This permits to place the strobe unit in the capacity of 30×120×10 mm.